1995
DOI: 10.1007/bf00222919
|View full text |Cite
|
Sign up to set email alerts
|

RFLP analysis of an Aegilops ventricosa chromosome that carries a gene conferring resistance to leaf rust (Puccinia recondita) when transferred to hexaploid wheat

Abstract: RFLP analysis has been used to characterise XM(v), a chromosome of Aegilops ventricosa present in a disomic addition line of wheat. This chromosome is known to carry a major gene conferring resistance to leaf rust (Lr). The analysis demonstrated that XM(v) is translocated with respect to the standard wheat genome, and consists of a segment of the short arm of homoeologous group 2 attached to a group 6 chromosome lacking a distal part of the short arm. Lr was located to the region of XM(v) with homoeology to 2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…While genotyping the mapping population, QCB36 (OR9900553) was found to carry the 2N v S‐2AS.2AL and 5B:7B chromosome translocations. These chromosome translocations have also been found in other VPM1‐derived lines (Badaeva et al, 2008; Bariana and McIntosh, 1994; Bonhomme et al, 1995). QCB36 was also found to carry the 1BS.1RL translocation (Zeller, 1973).…”
Section: Characteristicssupporting
confidence: 60%
“…While genotyping the mapping population, QCB36 (OR9900553) was found to carry the 2N v S‐2AS.2AL and 5B:7B chromosome translocations. These chromosome translocations have also been found in other VPM1‐derived lines (Badaeva et al, 2008; Bariana and McIntosh, 1994; Bonhomme et al, 1995). QCB36 was also found to carry the 1BS.1RL translocation (Zeller, 1973).…”
Section: Characteristicssupporting
confidence: 60%
“…Pchl has been used in wheat improvement and was transferred to several germplasms and cultivars (Roazon, VPM1, and Rendevous in Europe; and Madsen and Hyak in the United States). Bariana & Mclntosh (1993, 1994 and Bonhomme et al (1995) showed that VPM1 also had Ae. ventricosa-derived genes Lr37 for leaf rust resistance, Sr38 for stem rust resistance, and Yr17 for stripe rust resistance, which were derived from chromosome 6M v and mapped to the short arm of wheat chromosome 2A.…”
Section: Gb5from Ae Speltoidesmentioning
confidence: 99%
“…Molecular techniques now provide a considerable range of methods for identifying alien sequences in a particular species and hence of establishing the extent of introgression. Randon amplified polymorphic DNA (RAPDs), restriction fragment length polymorphisms (RFLPs) and microsatellite analysis have been used to examine nuclear DNA, chloroplast DNA (cpDNA) and mitochrondial DNA (mtDNA) to provide evidence of introgression occurrence ( Hillis 1987; Schmidt & Heslop‐Harrison 1993, 1996; Watanabe 1994; Bonhomme et al . 1995 ; Francis et al .…”
Section: Detecting Introgression and Hybridization In Plant Populationsmentioning
confidence: 99%